(untitled) (Indian Journal of Arid Horticulture, 2013)
Pomegranate (Punica granatum L.) is thought to be indigenous to the region of Iran where it was first cultivated in about 2000 B.C., but it spread to the Mediterranean countries at a very early date. Pomegranate is an important commercial fruit in India which is mainly grown in the Maharashtra, Gujrath, Karnataka, Rajasthan etc. Pomegranate flowers from late April until mid May, whereas maturity and ripening extends from mid September to November depending on the cultivars. Fruit growth is typically described as a single or double sigmoid curve reflecting changes in organ fresh weight. Other measures of growth (e.g. length, diameter) may give quite different growth curves (Commbe, 1976).